Effect of Khaya Senegalensis Leaves Extract against Freshwater Snail (Lanistes ovum Peters-1845) - Usman, Musa Aliyu, Shinkafi, Sa'adatu Aliyu* (Sokoto Journal of Medical Laboratory Science)
Toxicity experiment were conducted to evaluate the molluscicidal activity of aqueous leaf extract of Khaya senegalensis against freshwater snail (Lanistes ovum) for the control of fascioliasis disease in livestock. The toxic effect of the plant leaf extract was time as well as dose-dependent. There was a significant negative correlation between LC values and exposure periods thus, with the increase in mortality. The LC50 decreased from 614.28 mg/L (24 hours), 246.22 mg/L (48 hours), 163.11 mg/L (72 hours) to 100% mortality at (96 hours). However, aqueous leaf extract of K. senegalensis caused no mortality against Tilapia fish (Tilapia zilli) as non-target organism, it is environmentally safe, cheap, easily biodegradable and suitable for the control of snail vector of fascioliasis disease.